WUJUD KENYAMANAN BELAJAR SISWA, PEMBELAJARAN MENYENANGKAN, DAN PEMBELAJARAN BERMAKNA DI SEKOLAH DASAR - Wahyu Widodo (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2016)
Learning in primary schools are planned and practicedby the teacher. Nevertheless, the rate remains the quality of thelearning of the students. The quality of students' learningassessed based on fulfillment of the comfort element oflearning, learning fun and meaningful learning. Conveniencestudent learning can be realized with a class that is clean; classlighting was good; Comfortable room temperature (around 25º-28ºC); and ergonomic seating arrangement; the use ofinstrumental music; Low noise level class; classroom discipline;and structuring the learning community (student-teacher-parent)who support the learning process. Enjoy learning can berealized with the use of scientific approach, learning throughdistraction humor, and group learning method. Meaningfullearning can be realized through organizing theme, content andlearning materials are solid; preparation of teaching materialsthat are practical and attractive; use a scientific approach; useposter simple sentences; teachers' teaching skills; and theapplication of authentic assessment.